Enhancing Students’ Grammar Mastery Using Authentic Materials of the Tenth Grader of SMAN 1 Tiris - Retno Widyaningsih (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Grammar is an important English component that need to be mastered by senior high school students because it helps them in mastering other English skills. Therefore, it is revealed that the students is hard to learn it, especially the tenth grade students in SMAN 1 Tiris of academic year 2018/2019. It can be seen from their low average score, their score was 53. This score is below the minimum standard, meanwhile their minimum standard score was 70. The aim of this study is to improve students’ grammar mastery using authentic materialsof thetenth grade students of SMAN 1 Tiris in academic year 2018/2019. Classroom Action Research (CAR) is applied in this present study. The subjects of the research were 20 students of X MIPA 1. The subjects were given a treatment using authentic materials for about three meetings. After treatment, they were given a test consisting of 30 multiple choice questions to measure students’ grammar mastery.The result of the test showed significant different before and after taught by using Authentic Material. Students’ average score before treatment was 53, and after treatment was 86. It means that using authentic material helped the students in enhancing their grammar mastery. Practically, by conducting this research, the researcher expects that the result will help future researcher, teachers and learners. Further researcher can use the present study and develop the use of flashcards also evaluate some parts that needs to be revised. The further researcher also can make this study as a source for further research. This research also hopefully can help teacher to solve their problems in enhancing students’ achievement using authentic materials. The method is an effective way that make teacher easy to stimulate students’ comprehension and interest. Authentic materials also can stimulate students’ brain to catch some information easily. Keywords: Teaching and Learning, Authentic Materials, Grammar